Novel functionalized carbon nanotubes for improving the surface properties and performance of polyethersulfone (PES) membrane - Rahimpour, A.; Jahanshahi, M.; Khalili, S.; Mollahosseini, A.; Zirepour, A.; Rajaeian, Babak (Elsevier BV, 2012)
Amine functionalized Multi-walled carbon nanotubes (F-MWCNTs)/polyethersulfone (PES) membranes were prepared using phase inversion induced by immersion precipitation. Crude MWCNTs were chemically treated using strong acids (H2SO4/HNO3) and 1,3-phenylenediamine (mPDA) to produce the functional amine groups (single bondNH2) on their surfaces. F-MWCNTs with different concentration were blended in the casting solution containing PES, polyvinylpyrrolidone (PVP) and dimethylacetamide (DMAC). Pure water was used as non-solvent. The FTIR spectra indicated that the amine functional groups were produced on the surface of MWCNTs. The membranes prepared with different concentrations of F-MWCNTs were characterized using contact angle, field emission scanning electron microscopy (FESEM), scanning electron microscopy (SEM), atomic force microscopy (AFM) and permeation tests. The surface hydrophilicity of membranes was significantly improved by addition of F-MWCNTs in the casting solution. An increment in the porosity, pore size and surface roughness of the membranes was observed by increasing F-MWCNTs content up to 1 wt.%. Further addition of F-MWCNTs caused a reduction in porosity and roughness of formed membrane. The membranes prepared with 0.5 and 1 wt.% of F-MWCNTs showed higher performance than neat membrane. Addition of F-MWCNTs in the casting solution improved the BSA rejection and antifouling properties of PES membrane.